KONSEP NASIKH WA MANSUKH MENURUT SYAH WALI ALLAH AL-DAHLAWI DAN IMPLEMENTASINYA - Muhammad Rafi (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2020)
One interpretation discourse that is echoed by contemporary figures is a discourse on nasikh and mansukh. Until now, Mansukh's narrative discourse is still a problem. There are some groups who reject this concept and some groups accept it. These groups can be classified into 3 groups: 1) Ulama mutaqaddimin who receive naskh mansukh absolutely without limitations. 2) Ulama muta'akhkhirin who limits nasikh mansukh to certain verses. 3). contemporary scholars who reject the existence of mansukh nasikh. One of the scholars who believed in the concept of nasikh and Mansukh with certain limitations was Shah Wali Allah Al-Dahlawi. He is an Indian contemporary thinker, whose thinking is very progressive. In this article we will discuss the concepts of Nasikh and Mansukh according to Shah Wali Allah Al-Dahlawi and its application. The method used is a descriptive method in describing the thoughts of Shah Wali Allah Al-Dahlawi. In the perspective of al-Dahlawi the Mansukh naskh is actually in the Qur'an, but is only limited to 5 verses of the Qur'an, namely: QS. Al- Baqarah: 180, QS. Al-Baqarah: 234, QS. Al-Anfal: 65, QS. Al-Ahzab: 52 and QS. Al-Mujadilah: 12.